Investigating the Role of Food Tourism in Shaping Destination Branding : A Qualitative Research Perspective - Gupta, Sonal; Sajnani, Manohar; Gowreesunker, Vanessa GB (Prabandhan: Indian Journal of Management, 2024)
Purpose : The qualitative research paper delved into the dynamic interplay between food tourism and destination branding, aiming to understand how culinary experiences contributed to shaping the overall image of a destination. Design and Methodology : This study used a qualitative research design, conducting in-depth interviews with food tourists in Delhi to explore the impact of food tourism on destination branding. Data were collected from 25 participants, and thematic analysis was used to identify recurring themes and patterns. We used MAXQDA Pro Analytics software to analyze themes and a word cloud generator for the word cloud. Findings : The research findings revealed that food tourism transformed destination branding. The research examined the cultural, social, and economic aspects of food tourism, shedding light on how local cuisines and gastronomic experiences influenced tourists’ perceptions and contributed to the distinct identity of a destination. The analysis yielded 10 themes and 45 sub-themes, helping marketers build Delhi-NCR as a food tourism brand. Research Limitations : The limitations included a focus on a specific destination, subjectivity in data interpretation, a small participant pool, time limits, external influences, and an overemphasis on positive features. Addressing these limits and exploring new opportunities could significantly contribute to the conversation around food tourism and destination branding. Originality : This research offered original contributions to both academia and destination management. It unveiled the dynamic interplay between food tourism and destination branding, bridging gaps in the existing literature, and shedding light on a transformative aspect of modern tourism.